Neuropsychiatric symptoms in community-dwelling Mexican-Americans: results from the Hispanic Established Population for Epidemiological Study of the Elderly (HEPESE) study() - Salazar, Ricardo (Int J Geriatr Psychiatry, 2014)
OBJECTIVE: The Neuropsychiatric Inventory (NPI) is a well-established measure of psychopathology and frequently used in dementia studies. Little is known about its psychometric characteristics at a population level, particularly among Hispanics. We report the frequency of NPI symptoms in a community-dwelling older Mexican-American (MA) population cohort and the degree of symptom-related distress experienced by participant informants. METHODS: Participants were 1079 MA age 80 years and over residing in five southwestern states who were administered the NPI as part of wave-7 of the Hispanic Established Population for Epidemiological Study of the Elderly (HEPESE) conducted from 2010 to 2011. RESULTS: Nine hundred twenty-five informants rated NPI domains. Prevalence of neuropsychiatric symptoms (NPS) varied by symptom domain and ranged from agitation/aggression (32%) to euphoria/elation (5%). The overall rate of behavioral disturbances was 62.7%. On the other hand, 37.3% of informants reported no NPS. A significant fraction of the informants reported distress from the mood disorder cluster of the scale. CONCLUSIONS: A large percentage (>60%) of community-dwelling older MA have one or more informant-reported NPS. These symptoms have diagnostic, prognostic, and therapeutic implications. Although neuropsychiatric disorders may be the initial clinical manifestation of dementia and often appear before cognitive alterations, the high frequency of these symptoms in the HEPESE cohort may reflect a high prevalence of these disorders among community-dwelling MA. The pattern we observed also suggests relatively advanced stages of dementia.